The development of price-wise e-commerce enabled web site. - Salleh, Mazleena; Liow, Chong Wei; Tang, Boon Leong (Penerbit UTM Press, 2001)
Electronic commerce or e-commerce is a new paradigm that changes the traditional way of managing business whereby it allows buyers, individual or organization, to search for products anywhere in the world and makes deal electronically. The advancement of network technology and the exponential growth of Internet and World Wide Web have been the key driving force for the rapid growth of e-commerce. However, adopting e-commerce into the business management involves huge investment due to expensive applications software. This paper describes an alternative solution of implementing functional e-commerce enable Web site that is cost-effective. This is achieved by employing freeware tools that provide the same capability of commercial software. The system developed delivers all the required services of e-commerce transaction as well as security services. This paper also acts as a guideline to small local companies in implementing e-commerce.